CdIn2S4‐xSex Solid‐Solution Nanocrystal Photocatalyst: One‐Step Hydrothermal Synthesis, Controllable Band Structure, and Improved H2‐Evolution Activity. (16th March 2022) - Li, Zhiwei; Zhong, Wei; Gao, Duoduo; Chen, Feng; Yu, Huogen
Abstract: Metal sulfide solid‐solutions have served as one of the most promising photocatalysts due to continuously adjustable bandgap structure and light‐absorption performance. Herein, a novel quaternary CdIn2 S4‐ x Se x solid‐solution nanocrystal photocatalyst is prepared by one‐step hydrothermal synthesis, including the initial production of CdIn2 S4‐ x (SeO3 ) x and its in situ reduction of SeO3 2− to produce Se 2− by N2 H4 . It is found that the bandgap structure of CdIn2 S4‐ x Se x nanocrystals can be adjusted from 2.42 to 1.87 eV by varying the molar ratio of Se/S. Compared with pure CdIn2 S4, the CdIn2 S4‐ x Se x solid‐solution photocatalyst clearly represents excellent photocatalytic hydrogen production performance, while the CdIn2 S4‐ x Se x ( x  = 0.4) solid‐solution nanocrystal exhibits the optimal hydrogen‐production efficiency of 314.24 µmol h −1, which is 3.3 times superior to that of CdIn2 S4 (94.83 µmol h −1 ). It is found that the introduction of Se increases the charge density of S 2− to form electron‐enriched S (2+δ )−, which can promote the effective adsorption of H + for the following interfacial hydrogen‐evolution reaction. Meanwhile, the CdIn2 S4‐ x Se x solid‐solution nanocrystals have a higher conduction band and stronger visible‐light absorption ability, which is also essential for accelerating photocatalytic hydrogen‐production efficiency. This study may offer possibilities for developing high‐performance photocatalysts. Abstract : A novel quaternary CdIn2 S4‐ x Se x solid‐solution nanocrystal photocatalyst is prepared by a one‐step hydrothermal synthesis route via introduction of Se to adjust the band structure, visible‐light absorption, and photocatalytic H2 ‐evolution performance of CdIn2 S4 .